A study of water intake during endurance training - Kondo, K.; Suzuki, T.; Ito, H. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: Appropriate intake of water makes training more effective. It is also important in maintaining health. However, precise knowledge as to the optimal types of beverage and the optimal amounts required during training often is not possessed by athletes or coaches. Even when such knowledge is possessed, either the carbohydrate concentration of the beverage actually ingested is too low, or in some cases, the volume of the beverage is inadequate. Under such circumstances, the present study was undertaken to investigate the current status of water intake by cross-country skiers during training, with a goal of identifying what needs to be improved through analysis of the effects of endurance training on physiological variables.